A Comparative Linguocultural Analysis Of Synonyms, Antonyms, And Homonyms In English And Uzbek - Abdusalomova, Umidaxon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
The article offers a comparative linguocultural analysis of synonyms, antonyms, and homonyms in English and Uzbek. The study relies on representative text sampling, componential and pragmatic analysis, and contextual verification. The results demonstrate that evaluative meanings and etiquette norms systematically shape synonymy and antonymy, while culturally stabilized scenarios intensify homonymy-related ambiguity. The paper contributes implications for translation practice and bilingual lexicography.